Biological control of pathogenic fungi using Pseudomonas brassicacearum isolated from Aronia × prunifolia (Marshall) Rehder roots - Dunya Albayati; Ahmed Ismael Naqee Al-bayatı; İbrahim Özkoç; Luau Burhan Mustafa (International Journal of Secondary Metabolite)
Endophytic bacteria, which are the subject of this study, serve as natural antifungal agents in the struggle against fungal infections, offering an eco-friendly alternative to chemical fungicides. So, it was aimed to determine the antifungal capacities of endophytic bacteria from Aronia ×prunifolia roots in the study. 25 endophytic bacteria were isolated, and their ability to act as biocontrol agents was evaluated by measuring fungal growth inhibition and chemical properties. Later, bacteria that showed a positive effect were identified through 16S gene sequencing. The results showed that the LB2 bacteria had the greatest ability to inhibit the selected fungi and the biochemical tests showed that the bacteria were Gram-negative, did not form spores, their colonies were well defined, and they could break down starch and gelatin, which was later diagnosed as Pseudomonas brassicacearum according to phylogenetic relationships. This study is the first report on which P. brassicacearum was isolated from A. ×prunifolia roots for the first time. These findings contribute to our understanding of the potential of endophytic bacteria, particularly P. brassicacearum, as natural antifungal agents in plant and human protection, offering a promising and sustainable approach to combat fungal infections while reducing the use of chemical fungicides.